1992
DOI: 10.1093/eurheartj/13.suppl_d.17
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric investigation of human myocardium in arterial hypertension and valvular aortic stenosis

Abstract: Myocytic hypertrophy and increased perimyocytic fibrosis accompany intraventricular pressure overload (hypertension and aortic stenosis) in human hearts. Myocardial structure as a result of arterial hypertension, but not aortic stenosis, is also characterized by intramyocardial arteriole wall-thickening and increased perivascular fibrosis. Thus, distinct structural reaction patterns are noted in the cardiac hypertrophy associated with hypertension and aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 0 publications
3
44
0
4
Order By: Relevance
“…Intramural coronary vessels of patients with LVH attributable to AS, however, do not show evidence of vascular remodelling. 4 We have demonstrated that functional vascular compressive forces produced by an increase in LV filling pressure (extravascular resistance) and reduction in hyperemic diastolic perfusion limit MBF in those patients with AS. 2 It is hypothesized that increased extravascular resistance leads to deformation of vessels in the myocardial microvasculature by the mechanical motion of the beating heart and reduction in diastolic perfusion is responsible for myocardial ischemia in the absence of epicardial coronary artery stenosis, particularly in the subendocardium.…”
Section: Changes In Coronary Perfusion and Microcirculatory Function mentioning
confidence: 92%
See 1 more Smart Citation
“…Intramural coronary vessels of patients with LVH attributable to AS, however, do not show evidence of vascular remodelling. 4 We have demonstrated that functional vascular compressive forces produced by an increase in LV filling pressure (extravascular resistance) and reduction in hyperemic diastolic perfusion limit MBF in those patients with AS. 2 It is hypothesized that increased extravascular resistance leads to deformation of vessels in the myocardial microvasculature by the mechanical motion of the beating heart and reduction in diastolic perfusion is responsible for myocardial ischemia in the absence of epicardial coronary artery stenosis, particularly in the subendocardium.…”
Section: Changes In Coronary Perfusion and Microcirculatory Function mentioning
confidence: 92%
“…3 Perimyocytic fibrosis 4 and reduction in the number of resistance vessels per unit weight 5 may contribute to the reduction in CVR in LVH secondary to hypertension and hypertrophic cardiomyopathy. However, recent work suggests that increased systolic impedance to coronary flow as a result of perivascular compression 6 and, most importantly, a reduction in diastolic perfusion 2 are the primary contributors to impairment of coronary microcirculatory function in AS, predominantly because of curtailment in maximal myocardial blood flow (MBF).…”
mentioning
confidence: 99%
“…5 These pathological changes slow myocardial relaxation, which in turn diminishes normal ventricular filling and reduces coronary blood flow. 6,7 This is compounded by the increase in work and myocardial mass, which results in elevated myocardial oxygen demand and a decrease in microvascular density, 8 leading to reduced coronary vascular reserve.…”
Section: Clinical Perspective On Pmentioning
confidence: 99%
“…The media=lumen ratio and perivascular collagen area were determined separately for arterioles with external diameters < 40 mm, 40 -80 mm, and > 80 mm. 23 An average of 35 vessels per sample were evaluated.…”
Section: Heart Weightmentioning
confidence: 99%